PRE PRONOUN STUDY IN SURAT AL-BAQARAH - SALIM, SAHERA (Islamic Sciences Journal, 2023)
Praise be to Allah, Lord of the Worlds, and peace and blessings be upon the noble prophets and messengers of our Prophet Muhammad and his family and companions. The scholar of Arabic sciences, arts and semantics is puzzled in front of this rich language, and at the same time feels proud to be associated with this impulsive language in the meanings and vitality, and it is no wonder that it is the language of the Qur'an. (Oud conscience study in Surat Al-Baqarah) The choice of Surat Al-Baqarah as the subject of the study; because of the virtues and provisions, as scientists say that more than a thousand news and a thousand judgments and a thousand orders and a thousand forbidden. My study is an applied study that selects its examples from Surat Al-Baqarah, which gives a clear picture of the subject. It is not a statistical study; I have dealt with the topics of research in five topics: The first: introductory subject in the conscience, and the second: was studying the reference of verbal, moral and pronounced conscience, while the third section: it examines the promises of conscience on the plural, and the fourth topic: in the multiplicity of conscience reference, and then followed some questions Scattered in the conscience that were not enough to be an independent subject, and discussed the fifth topic: the issue of conformity of conscience to the word reference or its meaning. Finally, I hope that I have fulfilled this study its right, if that is what I hope, which is the conciliation of God and guidance, God prayed to our Prophet Muhammad and his family and companions and peace and our last prayer that praise be to Allah, Lord of the Worlds.